ASSESSING THE EFFICIENCY OF ENHANCING THE QUALITY OF MEDICAL CARE FOR RADIOACTIVE ACCIDENTS LIQUIDATORS - Nikolai P. Tikhomirov; Damir F. Ilyasov (Вестник Российского экономического университета имени Г. В. Плеханова)
In article discusses problems connected with assessing the efficiency of expenditure on medical care for liquidators of large radioactive accidents and persons who got the equivalent dose exceeding 100 m3v of sharp radiation. The authors developed methodology for assessing the dose borders of using this protective measure depending on the amount of per head expenses allocated for annual checking and diagnosing of cancer diseases. With the help of this methodology the authors prove the efficiency of enhancing the quality of medical care for participants of large radioactive accidents living on the territory of the Russian Federation.